Analysis of Students' Critical Thinking Skills in Physics Problems - Tri Ariani (Kasuari: Physics Education Journal (KPEJ), 2020)
This study aims to determine the proportion of students' level of critical thinking skills on the subject of Impulse and Momentum, any difficulties experienced by students to reach the level of critical thinking skills, and solutions to overcome the difficulties of students achieving critical thinking skills. This research uses descriptive qualitative research methods. The subjects of this study were 27 students taken by purposive sampling technique. Data collection techniques in this study are tests of critical thinking skills, interviews, and observation. Data analysis techniques using descriptive statistics. The results showed that each student's ability, high ability students 36.84%, medium ability 34.50%, low ability 22.80% divided into two categories of KBK 2 with a percentage of 52.63% and KBK 1 with a percentage of 23, 94%. From the results of the study also obtained the achievement of students every KBK indicator. Student achievement in the Interpretation indicator of 51.58% Analysis 18.75% Evaluation 13.87% Inference 31.48% Explication 14.19% and Self Regulation 26.85%. So KBK students as a whole are in the low category with a percentage of 31.38%. The cause of students 'difficulties in fulfilling CBC indicators is the limited ability of students to formulate and find other alternatives, the completion of students' answers is difficult to draw conclusions and connect substance between materials, and has not been studied in depth so students tend to be careless in solving problems. The solution that can be used is to provide more experience to students in terms of critical thinking skills and additional learning outside school hours.